Safety and Efficacy of STREAMLINE Canaloplasty with Phacoemulsification in Hispanic Adults with Open-Angle Glaucoma: 12-Month Outcomes - Lazcano-Gomez G; Orlich C; Batlle JF; Ison EM; Reynolds HP; Harbin M; Kahook MY (Clinical Ophthalmology, 2024)
Gabriel Lazcano-Gomez,1 Claudio Orlich,2 Juan F Batlle,3 Elysia M Ison,4 Heather P Reynolds,4 Med Harbin,4 Malik Y Kahook5 1Department of Glaucoma, Clínica Laser y Ultrasonido Ocular, Puebla City, Mexico; 2Clinica 20/20, San José, Costa Rica; 3Laser Center, Santo Domingo, Dominican Republic; 4New World Medical, Inc., Rancho Cucamonga, CA, USA; 5Department of Ophthalmology, University of Colorado Anschutz Medical Campus, Aurora, CO, USACorrespondence: Malik Y Kahook, Department of Ophthalmology, University of Colorado Anschutz Medical Campus, Aurora, CO, USA, Tel +1 720 848 2501, Email Malik.Kahook@cuanschutz.eduPurpose: To report the 12-month clinical outcomes in eyes with mild to moderate open-angle glaucoma (OAG) in Hispanic adults undergoing STREAMLINE Surgical System (STREAMLINE) canaloplasty combined with phacoemulsification.Patients and Methods: This was a prospective, multi-center, interventional clinical trial involving 45 eyes of 45 Hispanic adult patients receiving topical medical therapy for mild to moderate OAG and undergoing phacoemulsification surgery for visually significant cataracts at three sites. All eyes underwent a Screening visit, followed by medication washout and a subsequent Baseline visit to determine eligibility for STREAMLINE canaloplasty. The primary outcome was the proportion of unmedicated eyes with intraocular pressure (IOP) reduction of ≥ 20% from Baseline at Month 12. Secondary outcomes included mean change in IOP from post-washout Baseline, mean change in IOP-lowering medications compared to pre-washout Screening, and adverse events (AEs).Results: 43 eyes met the eligibility criteria for analysis and 40 eyes completed the 12-month visit. The mean (standard deviation) age was 68.7 (8.6 years), 76.7% were female, and 72.1% of the eyes were classified as having mild OAG. The mean number of IOP-lowering medications at Screening was 1.95 (0.82). After washout, the Baseline mean IOP was 23.0 (1.8) mmHg. At Month 12, 28/40 eyes (70.0%) remained medication-free, of which 27 (96.4%) had an IOP reduction of ≥ 20% from Baseline. The mean IOP at Month 12 was 15.3 (2.8) mmHg, a reduction of 7.8 (3.0) mmHg from Baseline (p< 0.001). The mean medication use at Month 12 was 0.63 (1.19) per eye, representing a mean reduction of 1.38 (1.03) medications from Screening (p< 0.001). Device- or procedure-related ocular AEs were mostly mild in severity and self-limited.Conclusion: STREAMLINE canaloplasty in combination with phacoemulsification provides clinically and statistically significant reduction in IOP and IOP-lowering medications in eyes with mild to moderate OAG in Hispanic adults.Keywords: STREAMLINE Surgical System, canaloplasty, intraocular pressure, minimally invasive glaucoma surgery, open-angle glaucoma